2019
DOI: 10.1016/j.ygcen.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

A unique role of thyroid hormone receptor β in regulating notochord resorption during Xenopus metamorphosis

Abstract: Tail resorption during anuran metamorphosis is perhaps the most dramatic tissue transformation that occurs during vertebrate development. Earlier studies in highly related anuran species Xenopus laevis and Xenopus tropicalis have shown that thyroid hormone (T3) receptor (TR) plays a necessary and sufficient role to mediate the causative effect of T3 on metamorphosis. Of the two known TR genes in vertebrates, TRα is highly expressed during both premetamorphosis and metamorphosis while TRβ expression is low in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Of particular special interest is intestinal remodeling, which involves degeneration of the larval epithelium via apoptosis and de novo formation of the adult intestinal stem cells in an organ autonomous, T3-dependent manner, thus offering an opportunity to study how adult organ-specific stem cells are formed during vertebrate development. Recent knockout studies on individual Xenopus tropicalis TR genes, TR α or TR® , have revealed important gene- and organ-specific roles during Xenopus metamorphosis [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 43 , 46 ]. Interestingly, the two TR genes can compensate for each other to enable tadpoles to complete metamorphosis in the absence of either TR gene despite their distinct expression profiles during natural development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular special interest is intestinal remodeling, which involves degeneration of the larval epithelium via apoptosis and de novo formation of the adult intestinal stem cells in an organ autonomous, T3-dependent manner, thus offering an opportunity to study how adult organ-specific stem cells are formed during vertebrate development. Recent knockout studies on individual Xenopus tropicalis TR genes, TR α or TR® , have revealed important gene- and organ-specific roles during Xenopus metamorphosis [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 43 , 46 ]. Interestingly, the two TR genes can compensate for each other to enable tadpoles to complete metamorphosis in the absence of either TR gene despite their distinct expression profiles during natural development.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of gene-editing technologies and the advancement in genome annotation for diploid Xenopus tropicalis, we and others have generated single ( TR α or TR® ) or double TR knockout (TRDKO) animals that have not only supported the dual-function model, but also provided novel details on the role of TRs during Xenopus development [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Interestingly, single TR knockout tadpoles could complete metamorphosis with delayed developmental progression of different organs, suggesting compensation between TRα and TR® .…”
Section: Introductionmentioning
confidence: 99%
“…5 ) that promote transcription of genes that drive metamorphosis ( Kulkarni and Buchholz, 2014 ; Sachs and Buchholz, 2019 ). For example, CS can induce expression of TRs to increase cellular sensitivity to the hormone signal ( Bonett et al, 2010 ; Kikuyama et al, 1993 ; Niki et al, 1981 ; Suzuki and Kikuyama, 1983 ), especially TR beta which is necessary for proper completion of metamorphosis ( Nakajima et al, 2019 ; Shibata et al, 2020a , 2020b ). The actions of CSs were synergistic with low or subthreshold doses of TH, producing strong induction of TR expression ( Bonett et al, 2010 ).…”
Section: Stress Hormones and Developmental Plasticitymentioning
confidence: 99%
“…With the advent of gene editing technologies that are applicable to amphibians, we and others have begun to investigate the role of endogenous TRs by using the diploid anuran X. tropicalis, which is highly related to X. laevis, especially with regard to metamorphosis (4,(28)(29)(30)(31)(32). Both TRa and TRb have been knocked out individually, and analyses of the single knockout animals have revealed interesting but distinct phenotypes (33)(34)(35)(36)(37)(38)(39)(40)(41)(42). Knocking out TRa leads to derepression of T3-inducible genes in premetamorphic tadpoles and premature initiation of metamorphosis, as reflected by limb morphogenesis, and also decreased response to exogenous T3 and reduced rate of metamorphic progression during natural metamorphosis (33,34,(37)(38)(39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has no detectable effect on tail resorption with overall time from fertilization to the completion of metamorphosis similar between wild-type (WT) and knockout animals. However, knocking out TRb has little effect on premetamorphic development and limb metamorphosis but delays tail resorption (35,36,42). Interestingly, both TRa and TRb individual knockout animals can complete metamorphosis with no apparently morphological defects in the resulting froglets, raising an interesting question whether TR is required for metamorphosis, especially considering that inactivating both TRa and TRb does not impair mouse embryonic development (43,44).…”
Section: Introductionmentioning
confidence: 99%